Description of Diet and Family Income in Toddler Children with Nutritional Status During the Covid-19 Pandemic Period in Anrong Appakka, Pangkep Regency (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2022)
Nutritional problems in children are cause by inadequate food intake due dietry factors and family income. The purpose of this study was to determine the diet and family income of children under five with nutritional status during the Covid-19 pandemic in Anrong Appakka Village, Pangkeje'ne District, Pangkep Regency. This type of research is quantitative observational with a descriptive observational approach. The population in this study were all children under five aged 13-59 months. The sampling technique used is total sampling. The results showed that during the Covid-19 pandemic, out of 145 children under five, most of the children under five or as many as 124 children under five (85.8%) had good nutritional status. The diet of children under five during the Covid-19 pandemic as many as 74 toddlers (51%) have a diet that is still classified as lacking and others or as many as 71 toddlers (49%) have a diet that is classified as sufficient. The family income status of children under five showed that of 145 children under five, almost all children under five or as many as 120 children under five (82.8%) experienced a decrease in family income and only a small part or 25 children under five (17.2%) did not experience a decrease in income during the pandemic. Covid-19.Gambaran Pola Makan Dan Pendapatan Keluarga Pada Anak Balita Dengan StatusGizi Selama Masa Pandemi Covid-19 Di Anrong Appakka, Kabupaten Pangkep